El desarrollo de la estructura productiva en Argentina, Brasil y México en 2018 - Marco Antonio Marquez Mendoza; Maritza Areli Velázquez Villalpando (Atlantic Review of Economics (ARoEc), 2024)
– This article argues that a developed productive structure is characterized by its complexity in inter - industrial relationships, which can be measured by the size of connections between sectors as well as by the economic distance that separates them. To evaluate this, the notion of "average propagation length" is used, representing the average number of steps needed for an external change in one sector to affect production in others. In Argentina, Brazil, and Mexico, it is observed that neoliberalism has not succeeded in maximizing the benefits of exports, and that the expansion of trade multiplier effects has been limited in terms of economic growth and job creation. Through the analysis of connections between sectors and the distance that separates them, the level of integration of the productive structure in these economies can be determined. In this study, Input - Output tables are employed to precisely assess this degree of integration in the mentioned economies.
Keywords: O40; F15; C67; O10; 330; Economic Growth; Trade; Productive Linkage; Structural Integration